Rancang Bangun Sistem Informasi Akuntansi Berbasis Desktop Penerimaan dan Pengeluaran Kas Sekolah - Hakim, Lukmanul; Saefudin, Dede Firmansyah; Wahyuni, Amelia Tri (PROFITABILITAS, 2021)
This study proposes a desktop-based accounting information system design model that can be implemented in educational institutions. Data collection methods are interviews and observations. The software development method used is Waterfall. The results showed that the accounting information system was successfully designed and implemented at SDIT   Jatisari, Karawang Regency. The design process is as follows: First, the scope of the designed information system is input for managing cash in and cash out, and managing reports. Second, the software requirements analysis stage used includes needs analysis, design use case diagrams and activity diagrams. Third, the design phase includes the preparation of entity relationship diagrams (ERD), logical record structure (LRS), file specifications, deployment diagrams, and user interfaces. Fourth, the implementation phase includes the preparation of code generation, blackbox testing, and hardware and software specifications.